Adopting the Public Accounts Committee Model for financial oversight in South African municipalities - a case study of the Public Accounts Committee in the City of Cape Town - Botes, Cobus (University of Stellenbosch, 2011)
Thesis (MPA)--University of Stellenbosch, 2011.